Stage 3 pyomyositis of the gluteus minimus; Staphylococcus aureus sepsis, autoanticoagulation, proximal femoral osteomyelitis and the role of surgical intervention. (29th November 2013) - Dacombe, Peter Jonathan; Evans, Jennifer; Gosling, Oliver Burton; Heal, James
Abstract : Primary pyomyositis is a rare bacterial infection of the skeletal muscle. Traditionally a tropical disease, it is increasingly described in westernised urban populations. The aetiology is due to transient bacteraemia in the presence of risk factors such as traumatised muscle, or immunocompromise. The condition presents in one of three stages, representing progression of disease severity. Intravenous antibiotic therapy is often sufficient for this disease at its early stage, but surgical drainage is necessary for advanced presentations. We report a severe case of stage 3 pyomyositis of the gluteus minimus, which led to Staphylococcus aureus sepsis, deranged liver function, acute kidney injury, autoanticoagulation and proximal femoral osteomyelitis in a healthy 64-year-old Caucasian man. This illustrates the potential severity of the disease, the life-threatening sequelae when diagnosis is delayed and the role of surgical drainage in averting the progression of systemic sepsis to end-organ dysfunction, disseminated intravascular coagulation and potentially death.